25. The LRRK2-R1441C mutation disrupts long-term potentiation-like plasticity in Parkinson's disease patients. Issue 12 (December 2017) - Dubbioso, R.; De Rosa, A.; Esposito, M.; Peluso, S.; Iodice, R.; De Michele, G.; Santoro, L.; Manganelli, F.
Abstract : Mutations in the leucine-rich repeat kinase 2 gene (LRRK2) account for up to 13% of dominant familial Parkinson's disease (PD) cases. The clinical and pathological features of LRRK2 -PD are often indistinguishable from idiopathic PD (iPD). Recent evidence pointed out that LRRK2 acts directly at the secretory and endocytic molecular machinery. Importantly, in southern Italy the R1441C mutation is the most frequent mutation reported so far. Based on the LRRK2-role on synaptic transmission, we aimed to investigate in vivo excitability and plasticity of the motor cortex by means of transcranial magnetic stimulation (TMS). Paired pulse TMS was used to investigate cortical excitability by using short intracortical inhibition and facilitation and short afferent inhibition paradigm. Intermittent theta burst stimulation (iTBS) was used to test long-term potentiation-like cortical plasticity (LTP). Eight LRRK2 -PD patients harboring the R1441C mutation and 11 iPD were tested on the more affected side in ON l-dopa therapy. We observed the lack of LTP-like motor cortex plasticity in R1441C- LRRK2 patients compared to healthy-subjects and with a similar profile observed for iPD patients. Motor cortex excitability profile did not exhibit any difference among the three groups. R1441C mutation disrupts motor cortex LTP-like plasticity in Parkinson's disease patients.